Pre-Service Teachers’ Integration into Teachers’ Community during Teaching Practicum - Afrianto (International Journal of Educational Best Practices, 2017)
Teaching practicum is a strategic place where pre-service teachers transform themselves from being pre-service teachers (PSTs) to become novice teachers. Data from a case study on how a group of PSTs experience integrate into teachers’ community during teaching practicum in Indonesian context shows that their journey is not linear; it encompasses a complex process, enriched by tension and conflict before some of them hold a sense of belonging to teachers community in their placement schools. Their ample engagement and participation with members of school community during teaching practicum program have effectively played as a significant factor behind their integration and identity transition.